NAVIGATING THE GLOBAL LANDSCAPE ON PROJECTBASED LEARNING AND 21ST-CENTURY SKILLS RESEARCH (2020–2023): A BIBLIOMETRIC ANALYSIS (Malaysian Journal of Learning and Instruction, 2024)
Purpose – This study aims to conduct a thorough examination and bibliometric analysis of the scholarly articles on PjBL (Project-Based Learning) and 21st-century skills published from 2020 to 2023. The analysis will specifically concentrate on the global distribution of these articles and identifying any prevailing research patterns or trends.Methodology – Utilizing “PjBL” and “21st-century skills” as search terms, the Scopus database was employed for the analysis encompassing annual publications, nations, institutions, authors, journals, references, and keywords in the field. This analysis was facilitated by VOSviewer and Microsoft Excel 2019 software.Findings – There has been a significant increase in publication volume between 2020 and 2023. Among the 2,472 articles within the Scopus database by the end of October 2023, Indonesia emerged as the primary contributor of publications among all nations. The VOSviewer indicates that the key issues revolve around, project-based learning (PjBL), pedagogy, critical thinking, education, sustainability, higher education, and 21st-century skills.Significance – A comprehensive analysis of the global landscape concerning project-based learning (PjBL) and, between 2020 and 2023, aims to uncover pivotal trends, emerging issues, influential authors, and seminal works in educational research. The anticipated outcomes hold the potential to offer multifaceted insights into PjBL and 21st-century skills, contributing to the exploration of innovative educational methodologies. Additionally, this study’s investigation of specific research inquiries aims to provide a holistic overview, further enriching the understanding of these crucial educational paradigms.